THE POSITION OF NEGERI SERDANG SULTANATE (1865-1946) TOWARDS ISLAMIC LEGAL DEVELOPMENT - Khoiri, Nispul (State Islamic University North Sumatra, 2022)
Abstract: This study aims to determine the form of legal policy of the Serdang State Sultanate in strengthening fiqh & fiqh proposals. Strategic steps of the Sultan’s legal policy in strengthening fiqh & fiqh proposals in the State of Serdang. The research is normative legal research and empirical law. These two types of research are deliberately carried out in order to search for deeper data. Normative research is theoretical research, comparative philosophical structures and others. The results of the study show: First, the Sultanate of Serdang has succeeded in putting in the form and construct of legal policies that are accommodative, open and democratic in nature. Second, the legal policies of the Serdang Sultanate in strengthening fiqh & fiqh proposals can be seen in: (1). Encouraging the creation of personal fatwas carried out by scholars in responding to various problems that arise. (2). Encouraging the creation of institutional fatwas, in which the Sultan has established an Islamic legal institution called the Syar’i Council, is an attempt by the Sultan to introduce the mufti institution as the institution responsible for giving religious and social fatwas.Keywords: Fiqh/Fiqh proposal, Legal policy, Sultan of Serdang